Abstract 9526: Fto Demethylase Mediates Altered N6-methyladenosine (m6a)-rna Modification in Human Failing Heart and Stressed-Induced Rat Cardiomyocytes - Dubey, Praveen K; Dubey, Shubham; Patil, Mallikarjun; Singh, Sarojini; Ahuja, Paras; pogwizd, Steven; Krishnamurthy, Prasanna (Circulation (New York, N.Y.), 2021)
BackgroundN6-methyladenosine (m6A) methylation is one of the important posttranscriptional modification of RNA, which affects RNA splicing, translation and stability. These modifications are dynamically regulated by writers, readers and erasers, and their alteration affects m6A modification and have shown to play key regulatory role in numerous biological processes. Fat mass- and obesity-associated (FTO) gene, known as a nucleic acid demethylase removes the methyl group from RNA and has been shown to be associated with progression of heart diseases. In this study, we determined m6A methylation in human failing heart, and evaluated if FTO regulates m6A-methylation of transcripts related to inflammation in cultured rat cardiomyocytes under various stress conditions. Methods and Resultsm6A RNA-methylation was increased in human failing hearts as compared to heart samples from non-failing subjects. Interestingly, failing hearts were associated with significant decrease in FTO mRNA and protein expression. Furthermore, cultured rat cardiomyoblasts (H9C2) cells exposed to stressors (hypoxia or isoproterenol) for 24hrs showed significant decrease of FTO and an associated increase in m6A-RNA methylation (dot blot analysis). To further test if stress-induced increase in m6A-RNA modification is mediated through FTO, we knocked-down FTO, treated with isoproterenol for 24hrs and evaluated m6A methylation status of RNA. Interestingly, dot blot analysis showed significant increase in m6A methylation levels and proinflammatory cytokines (IL6 and TNFa) in FTO knockdown cells as compared to scramble, both at basal level and after exposure to stress. Furthermore, we evaluated the effect of FTO on methylation of RNA transcripts that encode inflammatory cytokines. MeRIP assay (Methylated RNA immunoprecipitation using m6A antibody and analysis of m6A-transcript by qRT-PCR) demonstrated that the gene expression of proinflammatory cytokines, IL6 and TNF-alpha was significantly increased in FTO knockdown cells as compared to scramble control cells . ConclusionThis data suggests stress-induced loss of FTO in the heart might mediate m6A-RNA methylation and therefore potential leading to upregulation of inflammatory response in the myocardium.